2009
DOI: 10.1017/s0033822200034093
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with Outliers and Offsets in Radiocarbon Dating

Abstract: The wide availability of precise radiocarbon dates has allowed researchers in a number of disciplines to address chronological questions at a resolution which was not possible 10 or 20 years ago. The use of Bayesian statistics for the analysis of groups of dates is becoming a common way to integrate all of the 14C evidence together. However, the models most often used make a number of assumptions that may not always be appropriate. In particular, there is an assumption that all of the 14C measurements are corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
586
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 967 publications
(618 citation statements)
references
References 18 publications
4
586
0
5
Order By: Relevance
“…The chronological modelling described in this section has been undertaken using OxCal 4.2 (Bronk Ramsey 1995;2009a;2009b), and IntCal13 (Reimer et al 2013). This study is based on using the relative dating provided by the matrix of archaeological deposits to refine the calibration of a series of radiocarbon dates on samples from those layers.…”
Section: Chronological Modellingmentioning
confidence: 99%
“…The chronological modelling described in this section has been undertaken using OxCal 4.2 (Bronk Ramsey 1995;2009a;2009b), and IntCal13 (Reimer et al 2013). This study is based on using the relative dating provided by the matrix of archaeological deposits to refine the calibration of a series of radiocarbon dates on samples from those layers.…”
Section: Chronological Modellingmentioning
confidence: 99%
“…Because it is well established that, through the 'old wood' phenomenon (that is, the inbuilt age of wood in a living tree, as opposed to the storage age of a dead tree; e.g., Kurokawa et al, 2003;Vieira et al, 2005), all wood charcoal determinations will predate by an unknown amount of time the archaeological context of interest (e.g. Anderson, 1991;Spriggs and Anderson, 1993), we have opted to apply an outlier correction for charcoal dates, as informed by Bronk-Ramsey (2009b). The correction factor employed is based on the prior knowledge that the site, and thus the wood used, came from a rainforest setting, and applies the following formula: (Exp(1,À10,0), U(0,3),"t") whereby the exponential distribution runs from À10 to 0 with a time-constant of 1, ensuring modification only to those outliers that are older.…”
Section: Excavation Resultsmentioning
confidence: 99%
“…The published results, when modelled according with the published phasing, have poor agreement (model not shown), suggesting either a more complex taphonomy than has hither to be been recognised, or perhaps more likely (given the nature of the site) the redeposition of material. The model of the phased development of the site was re-run with the results subject to formal outlier analysis using the prior probability of 0.05 that each measurement was an outlier and the General T model (Bronk Ramsey 2009b). This analysis suggested that several measurements were problematic: OxA-9080, OxA-9159, and AA-29713 were all far too late for their position in the phased development of the site; OxA-9085 and OxA-9083 in contrast were too early for their position in the phased development of the site.…”
Section: Dunasbroc Lewismentioning
confidence: 99%